Internal liberty and validity of canonical marriage - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2013)
One of incapacitas ad matrimonium contrahendum forms is a serious absence of the evaluative insight as for significant matrimonial rights and obligations mutually transferred and accepted (can. 1095, n. 2 of the Code of Canon Law). Both in the doctrine and in the case law of the Roman Rota it is assumed that internal liberty (libertas interna) – except for intellectual cognition of the subject of matrimonial consent and critical capability, which is the proportional evaluation of the contracted marriage – constitutes one of evaluative insight elements. After appearance of doctrine and case law forming as regards influence of volitional factor dysfunction on validity of the matrimonial consent (the leading role played achievements of modern psychological and psychiatric sciences), the author discusses and analyses the notion of internal liberty (capability to decide with sufficient evaluation of motives and autonomy of will towards any impulse coming from inside), and then, focuses on absence of this liberty, which results in invalidity of the matrimonial consent (questioning among others, minimum of this liberty required for validity of the consent) and indicated reasons of this absence.